Melatonin Enhances Phenolics Accumulation Partially via Ethylene Signaling and Resulted in High Antioxidant Capacity in Grape Berries - Xu, Lili; Yue, Qianyu; Bian, Feng’e; Sun, Hong; Zhai, Heng; Yao, Yuxin (Frontiers in Plant Science, 2017)
This study assessed the primary impacts of exogenous melatonin (MT) treatment on grape berry metabolism. Exogenous MT treatment increased the endogenous MT content and modified berry ripening. Transcriptomic analysis revealed that the processes of polyphenol metabolism, carbohydrate metabolism and ethylene biosynthesis and signaling were the three most significantly altered biological processes upon MT treatment. Further experiments verified that MT treatment increased the contents of total anthocyanins, phenols, flavonoids and proanthocyanidins in berries. Additionally, the contents of 18 of the 22 detected individual phenolic compounds were enhanced by MT treatment; particularly, the resveratrol content was largely increased concomitantly with the up-regulation of STS gene expression. Meanwhile, MT treatment enhanced the antioxidant capacity of berries. On the other hand, it was indicated that ethylene participated in the regulation of polyphenol metabolism and antioxidant capacity under MT treatment in grape berries. In summary, MT enhances the polyphenol content and antioxidant capacity of grape berries partially via ethylene signaling.